C‐Glycosyltransferases catalyzing the formation of di‐C‐glucosyl flavonoids in citrus plants. (5th June 2017) - Ito, Takamitsu; Fujimoto, Shunsuke; Suito, Fumiaki; Shimosaka, Makoto; Taguchi, Goro
Summary: Citrus plants accumulate many kinds of flavonoids, including di‐ C ‐glucosyl flavonoids, which have attracted considerable attention due to their health benefits. However, the biosynthesis of di‐ C ‐glucosyl flavonoids has not been elucidated at the molecular level. Here, we identified the C ‐glycosyltransferases (CGTs) FcCGT (UGT708G1) and CuCGT (UGT708G2) as the primary enzymes involved in the biosynthesis of di‐ C ‐glucosyl flavonoids in the citrus plants kumquat ( Fortunella crassifolia ) and satsuma mandarin ( Citrus unshiu ), respectively. The amino acid sequences of these CGTs were 98% identical, indicating that CGT genes are highly conserved in the citrus family. The recombinant enzymes FcCGT and CuCGT utilized 2‐hydroxyflavanones, dihydrochalcone, and their mono‐ C ‐glucosides as sugar acceptors and produced corresponding di‐ C ‐glucosides. The K m and k cat values of FcCGT toward phloretin were <0.5 μm and 12.0 sec −1, and those toward nothofagin (3ʹ‐ C ‐glucosylphloretin) were 14.4 μm and 5.3 sec −1, respectively; these values are comparable with those of other glycosyltransferases reported to date. Transcripts of both CGT genes were found to concentrate in various plant organs, and particularly in leaves. Our results suggest that di‐ C ‐glucosyl flavonoid biosynthesis proceeds via a single enzyme using either 2‐hydroxyflavanones or phloretin as a substrate in citrus plants. In addition, Escherichia coli cells expressing CGT genes were found to be capable of producing di‐ C ‐glucosyl flavonoids, which is promising for commercial production of these valuable compounds. Significance Statement: Although di‐ C ‐glucosyl flavonoids have attracted a considerable amount of attention owing to their health providing benefits, the plant glycosyltransferase enzymes responsible for their biosynthesis are not yet known. We identified the C ‐glycosyltransferases responsible for di‐ C ‐glucosyl flavonoid biosynthesis in the citrus plants kumquat and satsuma mandarin and demonstrated that a single enzyme catalyzes both first and second C ‐glucosylation of flavonoids using either 2‐hydroxyflavanones or phloretin as substrates in these plants.